(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Jewish ethics is derived from the Torah, written and oral, and as such it is heteronomous, although the oral Law (halakhah) develops within the human progress of scientific knowledge. In Judaism and the Jewish Tradition the basic value is life: it serves as the framework for all the subsequent decisions in the moral practical sphere. There the first duty is always “to save life”, every life, and this means to protect and heal and take care of the integral unity of body and soul, at any stage of life. Scientists and doctors, nurses and patients, as well as halakhic decision makers, all are bounded to this fundamental value. Before being a right, to be and stay healthy is a duty that implies to choose a responsible style of life and a “preventive ethics” to prevent damages to our life.